New compound names in Lithuanian: diversity and formation peculiarities (the 2nd decade of the 21st century) - Sinkevičiūtė, Daiva (Vilnius University Open Series, 2022)
In the 2nd decade of the 21st century the Lithuanian stock of proper names is enriched with new compound names. They are formed in the following ways: a) from ordinary compound names, either changing or adding a new termination or altering the stems, e.g. Jo-gaĩl-is beside Jo-gáil-a, Dei-mant-ė́ja beside Deĩ-mant-ė, Ei-výl-ė beside Ei-vìl-ė; b) adding to a new name a stem used in other compound names, e.g. Ner-mìl-ė, Man-gìr-is; c) from Lithuanian stems of different origin (appellatives, hypocoristics, borrowings) added to the stem of other compound names, e.g. Bang-ì-mant-as: bang- < bangà ‘wave’, Jó-vyt-ė: vyt- < Výta, Výtė, Výtautė, Teo-mìl-ė: teo- < Teo, Teodorà; d) combining two new expansive stems, e.g. Ad-vità ← ad- < Adà, Adèlė + -vita < Vità, Jovità, Oks-mind-à ← oks- < Oksanà + mind- < Mìnda, Mìndaugė. These names continue the tendencies of the formation of names of the previous period. Most names are made without taking semantics into consideration. The stems are taken from popular names. The first stems are more diverse than the second, which coincide with frequent stems from the previous century. New stems are more frequent as first members of the compound. They are more often made from borrowings than from inherited lexicon. Some of them became stable new stems, etc. All this shows that the creation of new compound names remains an ongoing process.
Keywords: onomastics; anthroponymy; Lithuanian names; compound names; name trends